Characterizations of Swelling Granule of Clove Leaf (Syzygium aromaticum L.) Ethanol Extract - Wulandari, Ayu; Chintya, Gita; Tuldjanah, Muthmainah; Yanuarty, Rezky (Sciences of Pharmacy, 2024)
Cloves, scientifically known as Syzygium aromaticum L., hold promise as a potential antiulcer remedy due to their rich composition of compounds, including high levels of phenolic compounds such as eugenol, eugenol acetate, and gallic acid. To improve bioavailability in the gastric environment, this study focuses on optimizing and evaluating a swelling granule system derived from clove leaf extract. The granules were produced using wet granulation with Carbopol, HPMC, and their combination as polymer matrices. Results indicated favorable properties in the swelling granules, with the optimal composition of 210 mg Carbopol, 36 mg PVP, and 404 mg Avicel pH 101. These granules exhibited a uniform particle size distribution, with 90.1% below 149 µm and 9.9% distributed across mesh numbers 100, 80, and 40. The formula with Carbopol polymer showed superior flow rate, compressibility, and swelling capacity compared to other formulations. The interaction between Carbopol's C=O groups and HPMC's hydroxyl groups significantly influenced parameters, especially swelling capacity. Thus, when combining polymers, potential chemical or physical reactions should be considered. The wet granulation process effectively preserved secondary metabolite levels from clove leaf. Further tests are recommended to evaluate the granulation's effectiveness as a delivery system for clove leaf extract.